PENERAPAN METODE TREE LENGTH LOGGING SKALA OPERASIONAL DI AREAL TEKNIK SILVIKULTUR INTENSIF (STUDI KASUS DI PT SARMIENTO PARAKANCA TIMBER PROVINSI KALIMANTAN TIMUR) - Maman Mansyur Idris; Soenarno (BRIN Publishing, 2015)
Tree length logging method is an alternative way in timber harvesting to improve the efficiency of timber utilization and preservation of forests resources. This paper studies the performance of tree length logging application method in operational scale. Observation was conducted in the forest area of PT Sarimelati Parakanca Timber in East Kotawaringin Regency, Central Kalimantan Province, where Intensive Silvicultural Technique (SILIN) was applied. Data were collected through observation and direct measurements in the field including labor productivity and cost of felling and skidding, logging waste, exploitation factor (FE) and the damage of residual stand. Results show both felling productivities and skidding were improved. The felling capacity was improved into 60.535 m³/hour and skidding was improved into 31.931 m³/hour. The application of tree length logging can also reduce the felling cost into Rp 1,604.36/m³ and skidding cost into Rp 21,142.75/m³. The method also increase the exploitation factors (FE) into 0.93 and minimize the damage on residual stand by 20.70%.